Analysis of organizational culture, promotion, and compensation and its influence on job satisfaction - Adinda Ayu Lestari; Rama Chandra (Jurnal Riset Manajemen dan Bisnis, 2025)
This study aims to examine the influence of organizational culture and compensation on job satisfaction, and the mediating role of job promotion in these relationships. An associative research design was employed, and data were collected through a questionnaire distributed to 89 respondents. Path analysis using SmartPLS 3.0 was conducted to test the proposed hypotheses. The findings reveal that leadership, performance perception, and loyalty significantly and directly influence job promotion. Furthermore, both organizational culture and compensation have direct positive effects on job satisfaction. However, job promotion does not significantly affect job satisfaction, indicating that promotion does not mediate the relationships between leadership, performance perception, loyalty, and job satisfaction. These findings suggest that while organizational culture and compensation are critical drivers of employee satisfaction, promotion practices may not inherently enhance satisfaction, possibly due to unmet expectations or increased responsibilities associated with advancement. Since promotions don’t always increase satisfaction, companies must manage these processes thoughtfully by ensuring clarity in roles, providing support for new leaders, and aligning promotion criteria with employee expectations